2017
DOI: 10.4172/1989-8436.100056
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Dysbiosis and Role of Probiotics in Infant Colic

Abstract: Infant colic or excessive crying syndrome is a behavioral syndrome in 1-to 5-month-old infants involving long periods of inconsolable crying and fussing in otherwise healthy infants. Its etiology is unclear, but evidence regarding the implications of the infant gut microbiota is rising in importance.In this short review, we aim to expose recent findings on alterations in the microbiota of colicky infants which could trigger or facilitate infant colic, and summarize the clinical and mechanistical evidence of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Infant colic, a condition that severely impacts family quality of life, is correlated with altered abundance of enterobacteria, bifidobacteria, and lactobacilli. Several clinical trials report effectiveness of probiotics treatment for colic (Tintore et al, 2017). Third, effective interventions for various diseases with microbial products SCFAs (Gill et al, 2018) and BAs (Neuschwander-Tetri et al, 2015) have been reported with adults.…”
Section: Potential Intervention Strategies For Microbiota-related Dismentioning
confidence: 99%
“…Infant colic, a condition that severely impacts family quality of life, is correlated with altered abundance of enterobacteria, bifidobacteria, and lactobacilli. Several clinical trials report effectiveness of probiotics treatment for colic (Tintore et al, 2017). Third, effective interventions for various diseases with microbial products SCFAs (Gill et al, 2018) and BAs (Neuschwander-Tetri et al, 2015) have been reported with adults.…”
Section: Potential Intervention Strategies For Microbiota-related Dismentioning
confidence: 99%